Teachers’ Roles in Implementing the Merdeka Curriculum for Students’ Character Formation: A Qualitative Study at an Elementary School in Medan - Rima Purba; Destin Trimartin Ndraha; Maria Sihotang (Jurnal Pendidikan: Media, Strategi, dan Metode, 2025)
The Merdeka Curriculum emphasizes flexible, student-centered, contextual, and character-oriented learning. In elementary education, the success of this curriculum is strongly influenced by teachers’ ability to design meaningful learning, guide students’ behavior, integrate Pancasila values, and adapt learning strategies to students’ needs. This study aims to describe teachers’ roles in implementing the Merdeka Curriculum for students’ character formation at SD Negeri 065013 Medan. This study employed a descriptive qualitative design. Data were collected through observation and interviews with five teachers, supported by classroom observation involving Grade IV students. The data were analyzed thematically through data reduction, categorization, interpretation, and conclusion drawing. The findings show that teachers played several important roles in the implementation of the Merdeka Curriculum, namely as curriculum interpreters, learning facilitators, character models, learning designers, and student development guides. Teachers attempted to strengthen students’ discipline, responsibility, creativity, communication, collaboration, and respect through differentiated learning, classroom habituation, group work, worship routines, and Pancasila Student Profile-based activities. However, several challenges were found, including limited teacher readiness, low digital literacy, limited learning facilities, administrative workload, parental misunderstanding, and students’ difficulty in adapting to independent learning. The study concludes that the teacher’s role remains central in transforming the flexibility of the Merdeka Curriculum into meaningful classroom practice and character development.